Shared Decision-Making: An Autoethnography About Service User Perspectives in Making Choices About Mental Health Care and Treatment - Fox, Joanna (Frontiers in Psychiatry, 2021)
Shared decision-making (SDM) between mental health medication prescribers and service users is a central pillar in the recovery approach, because it supports people experiencing mental ill-health to explore their care and treatment options to promote their well-being and to enable clinicians to gain knowledge of the choices the service user prefers. SDM is receiving increasing recognition both in the delivery of physical and mental health services; and as such, is of significance to current practice. As an expert-by-experience with over 30 years of receiving mental health treatment, I have made many choices about taking medication and accessing other forms of support. The experiences of SDM have been variable over my career as a service user: both encounters when I have felt utterly disempowered and interactions when I have led decision-making process based on my expertise-by-experience. In this article, I recount two experiences of exploring care and treatment options: firstly, a discharge planning meeting; and secondly, the choice to take medication over the long-term, despite the side effects. The article will explore both opportunities and barriers to effective shared decision-making, as well as skills and processes to facilitate this approach. The need to balance power between service users and professionals in this interaction is highlighted, including the need to respect expertise built on lived experience, alongside that of clinical expertise. This narrative is framed within an autoethnographic approach which allows me to contextualize my personal experiences in the wider environment of mental health care and support.